2015
DOI: 10.1111/cxo.12311
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between clinical and laboratory methods assessing tonic and cross‐link components of accommodation and vergence

Abstract: Although different optometric tests of accommodation and vergence rely on the same basic principles, the results of this study indicate that clinical and laboratory methods actually involve distinct components. These differences, which are induced by methodological choices, must be taken into account, when comparing studies or when selecting a test to investigate a particular oculomotor component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…This significant accommodation should be taken into account during routine assessment (no cyclopedia) of refractive status among young people. The accommodative response in the Non-Cyc-0D was about 0.50 D greater than in the Cyc-0D with a reduced anterior chamber depth and an increased lens thickness, indicating that there was a minimal tonic accommodation in the Non-Cyc-0D eye 31 . Interestingly, the sub-foveal ChT in Non-Cyc-6D was reduced compared to Non-Cyc-0D or Cyc-6D while the ChT in Non-Cyc-0D was not different from the Cyc-0D, indicating that a greater accommodative response was associated with a thinner ChT while tonic accommodation had no effect on ChT.…”
Section: Discussionmentioning
confidence: 80%
“…This significant accommodation should be taken into account during routine assessment (no cyclopedia) of refractive status among young people. The accommodative response in the Non-Cyc-0D was about 0.50 D greater than in the Cyc-0D with a reduced anterior chamber depth and an increased lens thickness, indicating that there was a minimal tonic accommodation in the Non-Cyc-0D eye 31 . Interestingly, the sub-foveal ChT in Non-Cyc-6D was reduced compared to Non-Cyc-0D or Cyc-6D while the ChT in Non-Cyc-0D was not different from the Cyc-0D, indicating that a greater accommodative response was associated with a thinner ChT while tonic accommodation had no effect on ChT.…”
Section: Discussionmentioning
confidence: 80%
“…However, several other studies [15][16][17] have found no significant change in the AC/A ratio. Based on a previous study, 26 the coefficient of repeatability is 0.277 MA/D for the AC/A ratio. This variability may have masked any effect for the AC/A ratio.…”
Section: Discussionmentioning
confidence: 96%
“…It was calibrated for each participant at the beginning of the experiment. [21][22][23][24][25][26] To perform the calibration, the right eye was occluded with a Wratten filter while the left eye fixated a Maltese cross at infinity (viewed through the haploscope device); during fixation with the left eye, trial lenses (þ4 D to À4 D in 1-D step) were placed in front of the right occluded eye; measured refraction was compared to the refraction expected from the trial lenses considering a distance of 12 mm between the lens and the eye. A correction factor was obtained from the linear regression between PR II refraction and expected refraction.…”
Section: Assessment Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, vergence movements can be divided into a transient and a sustained part [92]. The transient part is fast and preprogrammed and initiates the response, while the sustained part is slow and under feedback control and brings the eyes to the final, accurate position [92, 93]. It could be possible that there is an effect of familiar size on vergence distance when the vergence movement is first programmed (in the transient part), but is corrected during the movement by the sustained part through the disparity feedback loop.…”
Section: Discussionmentioning
confidence: 99%